Research and development of Ayurvastra activewear - Golla, Alexandra, author; Morris, Kristen, advisor; Li, Yan, committee member; Sivakumar, Gaya, committee member (Colorado State University. Libraries, 2025)
This study integrates materials testing and consumer marketing analysis to establish the foundation for a sustainable activewear brand designed to enhance comfort and alleviate mild physical discomfort. Guided by a modified Design Thinking (DT) framework, the research is organized into three phases: Understand, Explore, and Materialize. The Understand phase examines current challenges in sustainable textiles and identifies emerging consumer needs in the activewear sector. The Explore phase encompasses comprehensive materials testing, design development informed by expert feedback, and a consumer survey assessing responses to sustainability-, health benefits-, and innovation-focused marketing messages. Finally, the Materialize phase synthesizes findings to inform future product and brand development. The results offer insights into the feasibility of using naturally dyed and bio-based textiles in performance apparel, reveal consumer preferences for sustainability and health-oriented design, and evaluate consumer responses to varied messaging conditions. By addressing both material functionality and consumer perception, this study provides multidimensional guidelines for advancing sustainable activewear that aligns with contemporary environmental and health values.